Ocena przydatności testu Patricka oraz innych testów funkcjonalnych w diagnostyce zespołu mięśnia gruszkowatego = Evaluation of Patrick's test and other functional tests in the diagnosis of piriformis muscle - Janusz Kocjan (Kazimierz Wielki University, 2016)
Kocjan Janusz. Ocena przydatności testu Patricka oraz innych testów funkcjonalnych w diagnostyce zespołu mięśnia gruszkowatego = Evaluation of Patrick's test and other functional tests in the diagnosis of piriformis muscle. Journal of Education, Health and Sport. 2016;6(8):711-718. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.61197 http://ojs.ukw.edu.pl/index.php/johs/article/view/3800     The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 05.08.2016. Revised 25.08.2016. Accepted: 28.08.2016.     OCENA PRZYDATNOŚCI TESTU PATRICKA ORAZ INNYCH TESTÓW FUNKCJONALNYCH W DIAGNOSTYCE ZESPOŁU MIĘŚNIA GRUSZKOWATEGO   EVALUATION OF PATRICK'S TEST AND OTHER FUNCTIONAL TESTS IN THE DIAGNOSIS OF PIRIFORMIS MUSCLE   Janusz Kocjan   Studium Doktoranckie Wydziału Lekarskiego w Katowicach, Śląski Uniwersytet Medyczny w Katowicach Doctoral Studium of School of Medicine, Medical University of Silesia, Katowice, Poland     Słowa kluczowe: zespół mięśnia gruszkowatego, test Patricka, test Freiberga. Key words: piriformis syndrome, Patrick test, Freiberg test.     Streszczenie             Zespół mięśnia gruszkowatego (ang. piriformis syndrome) jest stosunkowo rzadko występującym schorzeniem, które powstaje w wyniku przykurczu lub wzmożonego napięcia w obrębie mięśnia gruszkowatego. Diagnostyka tej jednostki chorobowej polega przede wszystkim na dokładnym badaniu fizykalnym. Przydatność poszczególnych testów funkcjonalnych wykorzystywanych w codziennej praktyce fizjoterapeutycznej nie jest dokładnie udokumentowana. Celem pracy jest ocena czułości i swoistości testu Patricka oraz pozostałych testów funkcjonalnych stosowanych w diagnostyce i rozpoznaniu zespołu mięśnia gruszkowatego. Grupę badaną stanowiło 20 osób w wieku 26-48 lat z rozpoznaniem zespołu mięśnia gruszkowatego. Grupa kontrolna składała się z 35 zdrowych osób w wieku 25-43 lat. Na potrzeby badania wykorzystano następujące testy kliniczne: test Freiberga, test Pace'a, test Beatty'ego, test FAIR, test Patricka oraz test opuszczania miednicy. Wykonano również badanie palpacyjne mięśnia gruszkowatego. Na podstawie uzyskanych rezultatów badania odnotowuje się, iż największymi wartościami czułości charakteryzuje się badanie palpacyjnie oraz test opuszczania miednicy. W przypadku pozostałych testów funkcjonalnych wartości czułości przedstawiały się na umiarkowanym poziomie, jednak wartość ich swoistości była wysoka. Wnioskuje się, iż bolesność palpacyjna oraz dodatni wynik w teście opuszczania miednicy i teście Freiberga przy jednoczesnym ujemnym wyniku pozostałych testów mogą być pomocne w wykrywaniu zespołu mięśnia gruszkowatego.     Abstract The syndrome piriformis muscle (called. Piriformis syndrome) is a relatively rare disorder that arises as a result of contracture or increased tension within the piriformis muscle. Diagnosis of the disease is primarily thorough physical examination. The usefulness of the various functional tests used in everyday practice physiotherapy is not exactly documented. The aim of the study is to evaluate the sensitivity and specificity of the test Patrick and other functional tests used in the diagnosis and diagnosis of piriformis muscle syndrome. The study group consisted of 20 people aged 26-48 years diagnosed with piriformis muscle syndrome. The control group consisted of 35 healthy individuals aged 25-43 years. For the study we used the following clinical trials: Freiberg test, Pace test, Beatty test, FAIR test and Patrick test lower pelvis. Also performed palpation piriformis muscle. Based on the results of the examination it recorded that the highest values of sensitivity is characterized by palpation examination and test lower pelvis. In the case of other functional tests of sensitivity presented at a moderate level, but the value of their specificity was high. It is proposed that the pain palpation and the positive result in the test, leaving the pelvis and Freiberg test, while a negative result of other tests may be helpful in detecting team piriformis muscle.